Between Poetry and Music: An Analysis of the Musical Settings of Poems from the Collection Tunes from Mousedale Dunes - Krevel, Alja; Denac, Olga (Trideset let literarne nagrade večernica, 2026)
This article presents an analysis of eleven poems set to music by Laura Zafred from the collection Tunes from Mousedale Dunes by Anja Štefan, as an example of the transformation of a literary text into an audio-musical medium. The songs are analysed from the perspective of rhythmic-melodic structure and expressive and timbral design of the arrangements. The article highlights how musical elements co-create the meaning of the text and shape the mood and character of individual songs. Music thus transcends a merely accompanying role and functions as an equal expressive element of the whole, confirming the autonomy of the musical interpretation of the literary text. In conclusion, the article emphasises the pedagogical value of musical settings within an educational context. The songs discussed represent a high-quality example of the integration of contemporary Slovenian children’s poetry and musical art, opening up space for active listening and children’s creative expression.